Influence of between‐limb asymmetry in muscle mass, strength, and power on functional capacity in healthy older adults. (16th August 2019) - Mertz, Kenneth H.; Reitelseder, Søren; Jensen, Mikkel; Lindberg, Jonas; Hjulmand, Morten; Schucany, Aide; Binder Andersen, Søren; Bechshoeft, Rasmus L.; Jakobsen, Markus D.; Bieler, Theresa; Beyer, Nina; Lindberg Nielsen, Jakob; et al.
Abstract : Purpose: Numerous daily tasks such as walking and rising from a chair involve bilateral lower limb movements. During such tasks, lower extremity function (LEF) may be compromised among older adults. LEF may be further impaired due to high degrees of between‐limb asymmetry. The present study investigated the prevalence of between‐limb asymmetry in muscle mass, strength, and power in a cohort of healthy older adults and examined the influence of between‐limb asymmetry on LEF. Methods: Two hundred and eight healthy older adults (mean age 70.2 ± 3.9 years) were tested for LEF (400 m walking and 30‐seconds chair stand). Furthermore, maximal isometric and dynamic knee extensor strength, leg extensor power, and lower limb lean tissue mass (LTM) were obtained unilaterally. Results: Mean between‐limb asymmetry in maximal muscle strength and power ranged between 10% and 13%, whereas LTM asymmetry was 3 ± 2.3%. Asymmetry in dynamic knee extensor strength was larger for women compared with men (15.0 ± 11.8% vs 11.1 ± 9.5%; P = .005) Leg strength and power were positively correlated with LEF ( r 2 = .43‐.46, P < .001). The weakest leg was not a stronger predictor of LEF than the strongest leg. Between‐limb asymmetry in LTM and isometric strength was negatively associated with LEF (LTM; r 2 = .12, P = .005, isometric peak torque; r 2 = 0.40, P = .03.) but dynamic strength and power were not. Conclusion: The present study supports the notion that in order to improve or maintain LEF, healthy older adults should participate in training interventions that increase muscle strength and power, whereas the effects of reducing between‐limb asymmetry in these parameters might be of less importance.